The German Middleway as Precursor for Single Embryo Transfer. A Retrospective Data-analysis of the Düsseldorf University Hospitalʼs Interdisciplinary Fertility Centre – UniKiD - Kliebisch, T. K.; Bielfeld, A. P.; Krüssel, J. S.; Baston-Büst, D. M. (Geburtshilfe und Frauenheilkunde, 2016)
Introduction: Patients receiving fertility treatment in Germany appear to be disadvantaged in comparison to those in other countries due to the restrictive Embryo Protection Act (“Embryonenschutzgesetz, ESchG”), which prohibits the selection of a “top” embryo. The so-called German Middleway (“Deutscher Mittelweg, DMW”) now provides for a liberal interpretation of the ESchG by allowing the culture of numerous pronuclear stages (2PN stage). Materials and Methods: Retrospective cohort study of 2 assisted reproduction treatment cycles in n = 400 patients between the ages of 21 and 45 years, either treated 2× conservatively or 1× conservatively and 1× liberally according to DMW. Results: Pregnancy was achieved in 35 % of patients in the DMW group and 31 % of controls. The birth rate among controls was 28.5 % and 30.5 % in the DMW group. Most pregnancies resulted from the culture of 4 × 2PN stages. Conclusion: Patients in the DMW group had significantly higher pregnancy and birth rates compared to their previous cycles despite significantly increased age and significantly fewer transferred embryos. Key factors were the number of 2PNs generated and the quality of embryos transferred. Thus it can be assumed that particularly older patients with adequate ovarian reserves will benefit from DMW, i.e. the transfer of fewer embryos of the best possible quality.
Keywords: ART; German Middleway; embryo protection act; blastocyst